Gestión económica y financiera para la asociación de producción agropecuaria del centro de acopio de la comuna San Antonio de Cumbijín. - Iza Anguisaca, Nataly Ximena (2020)
The agricultural production association at the collection center of the 'San Antonio de Cumbijin' commune is an organization controlled and monitored by the Superintendence of Popular and Solidarity Economy. The association is dedicated to collecting and cooling milk; it currently markets an average of 1,600 to 1,800 liters per day from different dairy companies. There are no adequate tools and techniques for managing economic resources so, it has experienced certain problems related to financial and economic management; and the lack of working capital in the association that has been affected daily. The general objective of this research is to evaluate the economic and financial management of the collection center, which will allow the development and improvement of the association by making appropriate decisions. The methodology used in the present research is qualitative because a documentary bibliographic review of the relevant aspects of financial management and the legal basis was carried out; also, an interview was carried out with the treasurer to obtain information about the internal situation of the association, which allowed to make value judgments concerning the historical facts of the collection center. On the other hand, based on the financial statements, the horizontal and vertical analysis was carried out, allowing the researchers to know how the association is in the financial aspect; it also helped determine the financial strategies. A feasibility study was carried out for one of the proposed strategies, in which an VAN of 19,576.92 dollars was obtained, the TIR was 39.81%, the cost-benefit ratio is $ 1.07 for each dollar invested; therefore, it can be deduced that the project is viable. Finally, the application of financial strategies is recommended to the association's board of directors since it will contribute to the organization to make timely decisions to improve financial management and the current situation, considering the economic feasibility, following the analysis carried out.